Potentials of photovoltaics and wind energy in India (considering Andhra Pradesh for photovoltaics and Kakulakonda for wind energy as case studies) - Radhika, Erram; Karmazsin, Etienne; Gupta, C.P.; Heredia , J.B.; EC (Bangkok : Asian Institute of Technology, 1995)
Because of continuing high growth of power demand and the inability of generation capacity. Concerns about the local and global environmental impacts of conventional generation technologies have compounded the predicament of India's chronic energy generation deficit. As part of the effort to address this situation, this study explores the prospects of non-conventional energy technologies to help close the chronic power deficit without the environmental consequences of conventional technologies. This study gives a comprehensive view of two non-conventional technologies wind energy and solar photovoltaics, highlighting the windy regions in India where wind-farms can be installed in large scale and the solar radiation data all over India. The existing projects sponsored by the government and private sector were also examined, exploring the present and future prospects of these resources in the country. Two regions are detailed in all aspects, Kakulakonda for setting a wind-farm and APSEB for examining various possible grid-PV integrated systems. Practical data such as indigenous suppliers, local technical manpower and incentives provided by the Government of India are also studied to get a practical usability to the work.
A thesis report submitted in partial fulfillment of the requirement for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1995
Keywords: Solar energy -- India -- Andhra Pradesh; Wind power -- India -- Kakulakonda